Analysis of the accidents and incidents occurring during the transportation of dangerous goods by railway transport - Batarlienė, Nijolė; Jarašūnienė, Aldona (Transport, 2014)
The article examines the accidents and incidents taking place while transporting dangerous goods by railway transport. The paper presents and considers research results indicating the way the respondents estimate the main factors related to risk in rail transport. Also, the correlation of the annual losses encountered by enterprises due to accidents and the losses caused by other factors are analysed. The work suggests recommendation measures for reducing accidents in railway transport while shipping dangerous cargoes.First Published Online: 16 Dec 2014